2019
DOI: 10.3389/fonc.2019.00499
|View full text |Cite
|
Sign up to set email alerts
|

Catechins-Modified Selenium-Doped Hydroxyapatite Nanomaterials for Improved Osteosarcoma Therapy Through Generation of Reactive Oxygen Species

Abstract: Osteosarcoma is the most common bone cancer with limited therapeutic options. It can be treated by selenium-doped hydroxyapatite owing to its known antitumor potential. However, a high concentration of Se is toxic toward normal and stem cells whereas its low concentration cannot effectively remove cancer cells. Therefore, the current study was aimed to improve the anticancer activity of Se-HAp nanoparticles through catechins (CC) modification owing to their high cancer therapeutic value. The sequentially devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…15,16 In one study, toxicity testing of Se-HAP loaded with the antioxidant catechin in human osteosarcoma cells (MNNG/HOS cell line) found that it exhibited antitumor activity provided by the generation of reactive oxygen species (ROS) via a caspase-3-dependent pathway. 17 This investigation seems to indicate potential for the treatment of bone cancers through the development of antitumor immunity and with minimal side effects to the stem cells, thereby reducing the probability of recurrence. Thus, taking advantage of the potential role of Se-HAP in the reduction of bone cancers, we synthesized an Se-HAP composite via a wet chemical route, in which two different types of samples were collected (after only precipitation and after precipitation followed by sonication).…”
Section: Introductionmentioning
confidence: 93%
“…15,16 In one study, toxicity testing of Se-HAP loaded with the antioxidant catechin in human osteosarcoma cells (MNNG/HOS cell line) found that it exhibited antitumor activity provided by the generation of reactive oxygen species (ROS) via a caspase-3-dependent pathway. 17 This investigation seems to indicate potential for the treatment of bone cancers through the development of antitumor immunity and with minimal side effects to the stem cells, thereby reducing the probability of recurrence. Thus, taking advantage of the potential role of Se-HAP in the reduction of bone cancers, we synthesized an Se-HAP composite via a wet chemical route, in which two different types of samples were collected (after only precipitation and after precipitation followed by sonication).…”
Section: Introductionmentioning
confidence: 93%
“…Nanotechnology is a burgeoning research field that has offered groundbreaking solutions for the diagnosis and treatment of OSA [ 21 ]. In this regard, a wide range of nanomaterials has been designed for the targeted treatment of OSA with the least cytotoxicity towards normal human cells [ 22 , 23 ]. As engineered nanomaterials, nanoparticles (NPs) have wide-spread applications in OSA diagnosis and treatment [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are also unclear aspects of nanotechnology restricting its broad-spectrum applications, the inherent unique properties of nanomaterials could help in improving their therapeutic efficacy against osteosarcomas (Turnbull et al, 2018;Zhang et al, 2018b). In addition to different nanoparticles, nanocellulose could also be used to replace the affected bone, like in the form of bone substitutes, as a matrix for impregnation of nanomaterials, and as a drug carrier (Khan et al, 2019) for treating different bone-related diseases. For instance, bisphosphonate-modified nanocellulose (pNC) could be used as a bone substitute for bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…The scaffolds demonstrated in vivo osteoinductivity and bone formation across the damaged site (Osorio et al, 2019a). Besides, nanocellulose could also be modified with anti-osteosarcoma metals or nanoparticles, for instance with selenium, strontium, and arsenic nanoparticles, where nanocellulose could not only function as a carrier for different drugs but also serve as a substitute for the damaged bone tissues (Khan et al, 2019;Luz et al, 2020). Both selenium and arsenic have been widely studied for their anticancer effects, where selenium has been found effective against osteosarcoma when doped with hydroxyapatite (Wang et al, 2016;Khan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%